Oral Disposition Index Predicts the Development of Future Diabetes Above and Beyond Fasting and 2-h Glucose Levels - Utzschneider, Kristina M; Prigeon, Ronald L; Faulenbach, Mirjam V; Tong, Jenny; Carr, Darcy B; Boyko, Edward J; Leonetti, Donna L; McNeely, Marguerite J; Fujimoto, Wilfred Y; Kahn, Steven E (Diabetes care, 2009)
OBJECTIVE:--We sought to determine whether an oral disposition index (DIO) predicts the development of diabetes over a 10-year period. First, we assessed the validity of the DIO by demonstrating that a hyperbolic relationship exists between oral indexes of insulin sensitivity and β-cell function. RESEARCH DESIGN AND METHODS--A total of 613 Japanese-American subjects (322 men and 291 women) underwent a 75-g oral glucose tolerance test (OGTT) at baseline, 5 years, and 10 years. Insulin sensitivity was estimated as 1/fasting insulin or homeostasis model assessment of insulin sensitivity (HOMA-S). Insulin response was estimated as the change in insulin divided by change in glucose from 0 to 30 min (ΔI₀₋₃₀/ΔG₀₋₃₀). RESULTS:--ΔI₀₋₃₀/ΔG₀₋₃₀ demonstrated a curvilinear relationship with 1/fasting insulin and HOMA-S with a left and downward shift as glucose tolerance deteriorated. The confidence limits for the slope of the loge-transformed estimates included -1 for ΔI₀₋₃₀/ΔG₀₋₃₀ versus 1/fasting insulin for all glucose tolerance groups, consistent with a hyperbolic relationship. When HOMA-S was used as the insulin sensitivity measure, the confidence limits for the slope included -1 only for subjects with normal glucose tolerance (NGT) or impaired fasting glucose (IFG)/impaired glucose tolerance (IGT) but not diabetes. On the basis of this hyperbolic relationship, the product of ΔI₀₋₃₀/ΔG₀₋₃₀ and 1/fasting insulin was calculated (DIO) and decreased from NGT to IFG/IGT to diabetes (P < 0.001). Among nondiabetic subjects at baseline, baseline DIO predicted cumulative diabetes at 10 years (P < 0.001) independent of age, sex, BMI, family history of diabetes, and baseline fasting and 2-h glucose concentrations. CONCLUSIONS:--The DIO provides a measure of β-cell function adjusted for insulin sensitivity and is predictive of development of diabetes over 10 years.